The diagnosis and treatment of adrenal insufficiency during childhood and adolescence. Issue 9 (15th April 2016) - Park, Julie; Didi, Mohammed; Blair, Joanne
Abstract : The diagnosis and treatment of adrenal insufficiency in childhood and adolescence poses a number of challenges. Clinical features of chronic adrenal insufficiency are vague and non-specific, and mimic many other causes of chronic ill health. A range of diagnostic tests are available for the assessment of adrenal function, all of which have advantages and disadvantages. Cortisol responses to these tests may vary with age and between genders. Knowledge of normal cortisol levels during health and ill health in childhood is also limited, and the cortisol replacement therapies available in clinical practice enable only crude mimicry of physiological patterns of cortisol secretion. An awareness of the limitations of diagnostic tests and treatments is important, and critical clinical assessment, integrating clinical and biochemical data, is essential for the diagnosis and treatment of children with suspected adrenal insufficiency. The aim of this review is to draw on data from clinical studies to inform a pragmatic approach to the child presenting with symptoms of chronic adrenal insufficiency. Clinical features of primary and secondary adrenal insufficiency, and syndromes associated with these diagnoses are described. Factors to consider when selecting a diagnostic test of adrenal function and interpretation of test results are considered. Finally, the limitations of cortisol replacement therapy are also discussed.